Molecular bases of the main CYP2D6 gene genetic polymorphisms, ethnic differences and pharmacological consequences - Casas, Paola M. (2007)
The CYP2D6 gene metabolizes approximately 25 % of drugs of clinical use and exhibits a marked genetic variation, thus according to the allelic variants carried by each individual three types of metabolism can be observed: poor (PM), extensive (EM) or ultrarapid (UM). There is also interethnic variation in the frequencies of PM, EM and UM individuals. Knowledge of the individual CYP2D6 metabolic status may be clinically and economically important and could provide the basis for a rational approach to drug prescription.